2016
DOI: 10.1109/tns.2016.2514364
|View full text |Cite
|
Sign up to set email alerts
|

System-Independent Characterization of Materials Using Dual-Energy Computed Tomography

Abstract: We present a new decomposition approach for dual-energy computed tomography (DECT) called SIRZ that provides precise and accurate material description, independent of the scanner, over diagnostic energy ranges (30 to 200 keV). System independence is achieved by explicitly including a scanner-specific spectral description in the decomposition method, and a new X-ray-relevant feature space. The feature space consists of electron density, , and a new effective atomic number, , which is based on published X-ray cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…In their study, Azevedo et al 6 demonstrated system-independence of the method and very good accuracy and precision for a set of standard materials with Z e < 15 with well-known physical parameters.…”
Section: Dual-energy X-ray Ct Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study, Azevedo et al 6 demonstrated system-independence of the method and very good accuracy and precision for a set of standard materials with Z e < 15 with well-known physical parameters.…”
Section: Dual-energy X-ray Ct Characterizationmentioning
confidence: 99%
“…where A(Z) is the atomic mass (g/mole) of the element Z. To approximate the atomic number of such a compound Azevedo et al 6 used the effective atomic number, Z e , defined as a non-integer atomic number that corresponds to an artificial element, for which the interactions are assumed to be modeled by the X-ray attenuation cross sections. The cross sections for the artificial element Z e are obtained by a linear interpolation between the cross section of the two adjacent elements in the periodic table:…”
Section: Dual-energy X-ray Ct Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of X-rays to penetrate deep inside a material makes it a useful tool to visualize the interior morphology of objects. X-ray imaging is very popular in applications such as industrial imaging [1]- [4], medical diagnosis [5], [6], and border security [4], [7]- [9]. A schematic representation of a typical cone-beam X-ray imaging system is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…µ (E, r) dr dE, (1) where µ(E, r) is the LAC of the object at X-ray energy E and spatial location r, L(i, j) is the line along which µ(E, r) is integrated, and S(E) is the X-ray spectral density such that E S(E)dE = 1 [4]. We will call the expression on the right side of the equality in equation 1as the ideal transmission functionT (i, j), i.e.,…”
Section: Introductionmentioning
confidence: 99%